Rancang Bangun Sistem Informasi Penjadwalan Produksi Berdasarkan Jadwal Pesanan Barang Pada PT. Bioli Lestari - Herry Susanto Kwee; Arifin Puji Widodo; Anjik Sukmaaji (Jurnal Sistem Informasi Universitas Dinamika, 2016)
Bioli Lestari is one of the company that run manufacturing industry. This company have problems at controlling their production schedule to fulfill customer product orders. The problem arise because their schedule based on raw material which available at the time, not based on costumer order. Production schedule problem cause company can’t give information about product finish due to the costumer. Based on problem explained before, a system that can handle customer orders and can make production schedule based on customers order being needed. In this case system use Shortest Processing Time (SPT) as a method to create production schedule, after that system will create production schedule based on customer orders which can help company to answer customers question about product orders finish due and can help company run production process based on customers orders